Fizičnogeografsko vrednotenje podeželskega prostora za kmetijstvo in pozidavo - Topole, Maja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The paper presents a method for evaluating rural space, especially for agriculture and built-up areas. The criteria of land suitability for arable surfaces, vineyards, orchards, meadows and built-up areas are selected geoecological factors. The stress is on Geographical Information System and onquantitative methods. The establishing the degree of significance of geo-factors in cases of different types of land use is of special importance.
Keywords: agrarna geografija; agriculture; kmetijska zemljišča; kmetijstvo; podeželje; raba tal; rural area; Slovenia; Slovenija; stavbna zemljišča; vrednotenje